أبجديات الغياب: نظرة في آليات الوعي المصري المعاصر - رشوان، ناجي (Natural Sciences Publishing, 2016)
تحاول هذه الدراسة الإجابة على تساؤل أساس يلخص مجمل أسئلتها وينسرب في خلفيات افتراضاتها ونتائجها، ربما يمكننا وضعه على النحو التالي: ما الذي يعبر عنه الانفصال القائم في الفعل الحضاري المصري المعاصر بين النظرية النقدية أو التنظير الفني من جهة، وأهدافها التطبيقية من جهة أخرى، وبينهما معا وثقافة الشارع المصري؟ أو بصورة أكثر عمومية: ما الذي يعبر عنه الانفصال القائم بين (المؤسسة) وفلسفة قواعدها الإجرائية من جهة، وأهدافها التي أنشأت من أجلها من جهة أخرى، وبينهما معا وحاجات الحياة اليومية أو متطلبات الخبرة المباشرة في العالم الحياتي العملي في مجتمعنا المعاصر؟ تسعى هذه الدراسة إذا إلى تقديم تفسير أولى لا يدعي الاكتمال لما أسمته على سبيل الإيجاز والمجاز حالة الوعي الحضاري الحالي في وجهين من وجوهه: الوجه الثقافي الإدراكي والوجه النفسي العاطفي، متخذة من مجال الإبداع النقدي والشعري منطقة عملها الأساس، ومن فلسفات الحضارة والنظرات النقدية عند هابرماس، ليوتار، وبوديلار، وفوكو، وهويسن، وإيهاب حسن، وإدوارد سعيد، ولندا هاتشن، وبارت، وبول دي مان، وغيرهم أطرها المرجعية المبدئية. يحاول الجزء الأول في هذه الدراسة الوقوف على تعريف مبدئي لحالة الانفصال هذه وتحليل آليات وجودها حال فعلها، ومناهج تبديها في النظرة الفنية والحضارية العامة على حد سواء، متخذا من مفهوم (البنية) "Structure" تعريفا واصفا لهذا الانفصال ومظاهره الوعيية. ويحاول هذا الجزء أيضا أن يقدم نقدا موجزا لهذا المفهوم من خلال تبيان أثره على الوعي الحضاري المعاصر وعواقب تبني الفكر له في النظرية الفنية والنظرة النقدية على حد سواء. أما الجزء الثاني فيحاول تحليل ما يراه بوصفه أصول حالة الانفصال هذه وأسباب وجودها واستمرارها وصور هذا الوجود المختلفة والمتنوعة في الفعل الحضاري العملي وخلفياته في الثقافة المعاصرة متخذا من مفهوم السرديات الكبرى "Grand Narratives" عند ليوتار إطاراً عاماً له في تعريف أحد جوانب هذه الأسباب والأصول وهو ما أسماه هذا الفصل (سردية) الوعي المصري المعاصر. أما الجزء الأخير فيعرف قسمه الأول جانباً أخر من جوانب تلك الأسباب والأصول متخذا من مفهوم التشبيهية "Simulacra" عند المنظر الفرنسي جان بوديلار أساس عاما له، ويناقش قسمه الثاني والأخير بعض الأفكار والتصورات بثقافة الغرب المعاصر أو ما يعرف بـ ما-بعد-الحداثة رغبة في الإيحاء بموجودات وعيية أخرى، وفي التمثيل على هذا الوجود، ومن ثم محاولة كشف الطرائق التي يمكن لأنواعها العامة الوصول إلى حالة (الوعي بالوعي) أو (الانعكاس على الذات) التي تراها هذه الدراسة حلا عمليا يمكنه فتح الباب أمام محاولات مواجهة أعراض الانفصال والترهل الحضاري السائدة في مجتمعنا الحالي. وعلى الآن أن أعرف مجموعة من المفاهيم والتعبيرات التي استخدمها هذا البحث بصورة متكررة والتي أرى في تعريفها الآن تمهيدا مناسبا يجعل من مواجهتها في نص الدراسة أمرا أقل ضريبة على القارئ والباحث على حد سواء. ما أعنيه بتعبير (الوعي الحضاري) يشبه ما يعنيه لوسيان جولدمان بتعبيره (العقل الجمعي) {1} أو ما يعنيه فوكو بتعبيره (الخطاب){2}، من حيث افتراضه مجموعة معينة من العوامل والصفات المنهجية العامة يشترك فيها أفراد مجتمع أو لسان معين، إلا أنه يختلف عنهما في تحديده جانباً واحداً من هذا العقل وحقلا واحدا من حقول هذا الخطاب ألا وهو الجانب الحضاري أو الحقل الحضاري؛ أي جانب أو حقل الفعل الاجتماعي الغائي وخلفيته الوعيية. فالوعي الحضاري إذا-في تعريفه المبدئي - يشير إلى المناهج التركيبية والصفات الفكرية والمبادئ النفسية التي على أساسها يعرف الفرد (مكانه الحضاري) في المجتمع (تاجر، شاعر، مدرس، رب أسرة، أعزب- تقليدي، متحرر، متمرد، متبع للأخلاق السائدة، رحيم، عادل، متفهم-إيجابي، فاعل، سلبي، مستسلم- محب للفنون، سطحي، عميق... إلخ)، أي دوره الفكري، والإنساني، والسياسي، والثقافي والاقتصادي حسب ما يتبدى في فلسفة ونوع وقيمة وحجم فعله الاجتماعي إن سلبا أو أيجابا ومن ثم لا يختص الوعي الحضاري بالفكر المجرد أو الرؤية الشخصية إلا لو تبدى هذا الفكر وتلك الرؤية في فعل ما، أو خرجا من حيزهما الشخصي إلى طرف أخر في المجتمع، وهكذا يختص هذا التعبير بكل تلك الأفعال دون استثناء فيها، أو تفضيل بينهما، ومن ثم يكون افتراضنا المبدئي الكامن خلف هذا التعبير هو أن كل فعل خارج عن الفرد إلى مساحة اجتماعية ما أيا كان حجمها هو فعل حضاري بالضرورة. أما تعبير (الوعي الثقافي) فيشير إلى جانب واحد من هذا (الوعي الحضاري) هو الجانب الإدراكي، ومن ثم يتضمن خصائص ومبادئ وصفات الإدراك الكامنة في الوعي الحضاري للفرد في لسان أو مجتمع ما، والتي على الرغم من إمكانية اشتراك جماعة لغوية ما في وجودها–أي هذه الخصائص والمبادئ والصفات–هي لا تزال خاصة بالفرد وحده، حتى لو تطابقت تطابقا كاملا مع مثيلاتها لدى الجماعة، أو افترض فيها ذلك افتراضا، لاحتوائها على بعد ذاتي لا يمكن تجنبه وهو البعد النفسي، ينطبق هذا الوصف بدوره على تعبيري (الوعي النقدي) و(الوعي الفني) كليهما؛ إذ أنهما يمثلان بدورهما جانبين من جوانب (الوعي الثقافي)، ومن ثم يحملان صفاته وحدوده العامة.
This paper seeks to answer a basic question informing its general hypnotizing and conclusions, which may be put as such: The obvious detachment in contemporary Egyptian cultural parxis between critical practice; theory/ theorizing, and artistic expression, on the one hand, and between both and the culture of everyday life, is only a symptom of a larger and more profound rupture. This rupture is between "the establishment" at large, philosophical under-layers of its practiced procedures included, and the main aims of its constitution, on the one hand, and between both and the needs of Egyptian everyday life or the demands of every-day experience in the practical life-world in our contemporary society, on the other. The main question of this paper, thus, is; what is this rupture or detachment mean; and how does it express itself; and, most importantly why? This paper, thus, seeks to offer a preliminary explanation, in no way complete, to what it has called in abbreviation, perhaps even reduction: the condition of contemporary cultural consciousness in only two of its apparent facades: its conceptual perceptual, and its emotional psychological. It will take literary criticism and poetic expression as its main felid of application as well as utilize some of the current international insights into culture and criticism in the works of such philosophers and critics as Derrida, Habermas, Lyotard, Baudrillard, Said, Ihab Hassan, Linda Hutcheon, Barthes, Paul De Man, and others. The first part of this study attempts to formulate a general definition of this state of "detachment" as well as the mechanisms of its existence in action. This will include attempting to redefine this states’ modes of manifestation in the artistic and general cultural expressions, offering "structuralism" at large, and this paper’s concept of "structure" in specific, as the main definition of this "detachment’ and its consequences. Part 2 will attempt to analyze what it sees as the perceptual roots of this detachment and the more specific reasons of its existence and continuation in the current practice of daily life and culture using Lyotard’s concept of "grand-narratives" as a general guideline. It will argue, that Lyotard’s concept helps to determine the second aspect or feature of this state of rupture or detachment; namely the narrativeness of this consciousness. Part 3, in its first section, attempts to define yet another aspect of this separation and detachment in the current cultural consciousness. Using Baurrillard’s concept of "Simulacra", this section argues for the simulative nature of this consciousness as another reason for this cultural separation and detachment. The second section of this part offers a re-definion of some of the most basic concepts of what has been termed in the past few decades as "postmodernism"; or the cultural logic of contemporary Western consciousness. This argues for the presence of different cultural conceptual frameworks by contrast, and the exemplification of such presence, aiming to reach a state of what this paper calls ‘consciousness of consciousness" or "self-re-definition", which this paper sees as the only solution for this state of cultural detachment an disintegration prevalent in our society. Let us now outline few general terms and concepts repeatedly used by this paper in order to increase clarity for reception. What is meant by "Civil consciousness" is similar to what Lucien Goldman means by the term "mentality", or Foucault by "discourse", in so much as they both presuppose a set intellectual modes and features characterizing a group of people. However, it differs from this in so much as it chooses only one aspect of that mentality or discourse; that is the conceptual, and its political echoes. "Civil Consciousness", then, covers certain number of compositional perceptual methods and modes based on the individual’s civil definition of herself in society (merchant, teacher, poet, family man, single, traditional, liberal, just, positive, ...etc.); that is, her .civil role; political, intellectual and economic, as apparent in her social acts, either negative or positive. In this sense, a "civil consciousness" is not concerned with the abstract thought of the individual unless it has manifested itself in a set of social and/or cultural acts. Our basic presupposition, then, that every act emanating from an individual and, thereby, radiating onto a social space is necessarily a civil act regardless of volume or value. "Cultural consciousness", on the other hand, refers to only one aspect of that general "civil consciousness"; that is the perceptual, covering, in the main, methods of perception as implied by an individual or a group in a certain society at a certain historical moment. Since it necessarily entails a definite psychological component, a "cultural consciousness" is necessarily individual regardless of how common.
Keywords: الفكر الفلسفي -- هابرماس، يورغن -- البنيوية -- النقد الأدبي